A Decade of Oil Discovery in Ghana: Implications for Politics and Democracy - Graham, E.; Gyampo, R.E.V.; Tuokuu, F.X.D. (Ghana Social Science Journal, 2020)
Ghana discovered oil in June 2007 and commenced production in December 2010 under a peaceful democratic political order that is being hailed by all across the world as a beacon of hope. Based on a desktop review, this paper examines how oil affects politics and democratic development in Ghana. It argues that even though there are efforts to protect Ghana from the 'oil curse' or potential adverse socio-economic effects of oil production, conscious efforts have not been made to check the possible impact of oil production on the nation's democratic gains. Consequently, oil production has resulted in tendencies that undermine democratic development, including politics of resource-patronage; high spending on social services such as infrastructure; high borrowing that increases national debt; and high corruption and perception of corruption and security threats. The paper concludes with some theoretical and policy implications of the findings for oil-producing countries in Sub-Saharan Africa.
Ghana Social Science Journal, 17(1), 31-57
Keywords: Oil and gas; Politics; Resource curse; Democracy; Ghana